Предмет: Алгебра,
автор: darya77r
1. Упростите выражение:
1) а) (5e - 7) + (2- e); б) (8f + 12) - (7- 6f);
2) а) (7p2 - 1) + (2- 6p - p2); б) (11- 16q2) - (q3- q2 + 8).
Ответы
Автор ответа:
0
1) а) (5e - 7) + (2- e) = 5е-7+2-е=4е-5;
б) (8f + 12) - (7- 6f) = 8f+12-7+6f=14f+5;
2) а) (7p2 - 1) + (2- 6p - p2)=7p2-1+2-6p-p2=6p2-6p+1;
б) (11- 16q2) - (q3- q2 + 8) = 11-16q2-q3+q2-8 = -q3-15q2+3.
б) (8f + 12) - (7- 6f) = 8f+12-7+6f=14f+5;
2) а) (7p2 - 1) + (2- 6p - p2)=7p2-1+2-6p-p2=6p2-6p+1;
б) (11- 16q2) - (q3- q2 + 8) = 11-16q2-q3+q2-8 = -q3-15q2+3.
Похожие вопросы
Предмет: Физика,
автор: alinakologrivaa
Предмет: Литература,
автор: itsreallygay
Предмет: Українська мова,
автор: kokov0029
Предмет: Химия,
автор: denisgrunin97